Innovation dynamics and fiscal policy: Implications for growth, asset prices, and welfare - Michael Donadelli; Patrick Grüning (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
We study the general equilibrium implications of different fiscal policies on macroeconomic quantities, asset prices, and welfare by utilizing two endogenous growth models. The expanding variety model features only homogeneous innovations by entrants. The Schumpeterian growth model features heterogeneous innovations: "incremental" innovations by incumbents and "radical" innovations by entrants. The government levies taxes on labor income and corporate profits and supplies subsidies to consumption, capital investment, and investments in research and development by entrants and, if applicable, incumbents. With these models at hand, we provide new insights on the interplay of innovation dynamics and fiscal policy.
urn:nbn:de:hebis:30:3-431627
Keywords: E22; G12; H20; I30; O30; 330; endogenous growth; asset pricing; government; fiscal policy; heterogeneous innovation